Mesolimbic Dopamine Transients in Motivated Behaviors: Focus on Maternal Behavior - Robinson, Donita L.; Zitzman, Dawnya L.; Williams, Sarah K. (Frontiers in Psychiatry, 2011)
Phasic activity of the mesolimbic dopamine pathway – burst firing of dopamine neurons and the resulting dopamine release events at striatal targets – have been associated with a variety of motivational events, such as novelty, salient stimuli, social interaction and reward prediction. Over the past decade, advances in electrochemical techniques have allowed measurement of naturally-occurring dopamine release events, or dopamine transients, in awake animals during ongoing behavior. Thus, a growing body of studies has revealed dynamic dopamine input to ventral striatum during motivated behavior in a variety of experimental paradigms. We propose that transient dopamine release may be important neural signals in pup-directed aspects of maternal behavior, as preliminary data suggest that dopamine transients in dams are associated with pup cues. Measurements of dopamine transients may be useful to investigate not only typical maternal behavior but also maternal inattention induced by drug exposure or stress.